Mitochondria: An Integrative Hub Coordinating Circadian Rhythms, Metabolism, the Microbiome, and Immunity - Aguilar-López, Bruno A.; Moreno-Altamirano, María Maximina Bertha; Dockrell, Hazel M.; Duchen, Michael R.; Sánchez-García, Francisco Javier (Frontiers in Cell and Developmental Biology, 2020)
There is currently some understanding on the mechanisms that underpin the interactions between circadian rhythmicity and immunity, metabolism and immune response, and circadian rhythmicity and metabolism. In addition, a wealth of studies has led to the conclusion that the commensal microbiota (mainly bacteria) within the intestine contributes to host homeostasis by regulating circadian rhythmicity, metabolism, and the immune system. Experimental approaches on how these four biological domains interact with each other have mainly focused on any two of those domains at a time and only occasionally on three. However, a systematic analyses on how these four domains concurrently interact with each other seem to be missing. We have analysed current knowledge that signpost a role of mitochondria as a key hub that supports and integrates activity across all four domains: circadian clocks, metabolic pathways, intestinal microbiota, and the immune system, coordinating their integration and crosstalk, providing a new perspective for more systematic experimental approaches.